The Relationship Between Organizational Culture, Motivation, Knowledge Sharing On Student Participation in Mbkm Program in State Universities - Ardianti, Vika; Sunarni, Sunarni; Timan, Agus (Universitas Negeri Malang, 2024)
Abstract : Student participation will have an impact on the sustainability of the MBKM program in the long term. However, it cannot be denied that the level of student participation is influenced by several factors including external and internal factors. One of the external factors that can affect the level of student participation is organizational culture and knowledge sharing. While the internal factor is motivation that comes from within students. This study aims to analyze the relationship between organizational culture, motivation, knowledge sharing on student participation in the MBKM program. The research population was taken from 2019 batch students of the Faculty of Education, State University of Malang. The sample used was 40 students by utilizing random sampling technique. Data collection was carried out by utilizing a questionnaire and disseminated using WhatsApp. While the data analysis used is the T test, F test, and the coefficient of determination test. The results showed that there was a relationship between organizational culture, motivation and knowledge sharing on student participation in the implementation of the MBKM program at State UniversitiesAbstrak : Partisipasi mahasiswa akan berdampak pada keberlangsungan program MBKM dalam jangka panjang. Namun tidak dapat dipungkiri bahwa tingkat partisipasi mahasiswa dipengaruhi oleh beberapa faktor diantaranya faktor eksternal dan internal. Salah satu faktor eksternal yang dapat mempengaruhi tingkat partisipasi mahasiswa adalah budaya organisasi dan berbagi pengetahuan. Sedangkan faktor internal adalah motivasi yang berasal dari dalam diri siswa. Penelitian ini bertujuan untuk menganalisis hubungan budaya organisasi, motivasi, berbagi pengetahuan terhadap partisipasi mahasiswa pada program MBKM. Populasi penelitian diambil dari mahasiswa Fakultas Ilmu Pendidikan Universitas Negeri Malang angkatan 2019. Sampel yang digunakan sebanyak 40 siswa dengan memanfaatkan teknik random sampling. Pengumpulan data dilakukan dengan memanfaatkan kuesioner dan disebarluaskan melalui WhatsApp. Sedangkan analisis data yang digunakan adalah uji T, uji F, dan uji koefisien determinasi. Hasil penelitian menunjukkan bahwa terdapat hubungan antara budaya organisasi, motivasi dan berbagi pengetahuan terhadap partisipasi mahasiswa dalam pelaksanaan program MBKM di Perguruan Tinggi Negeri.